POTENTIAL OF ORGANIC PRODUCTION FROM THE PERSPECTIVE OF YOUTH IN SERBIA - Bajagić, Marija; Stošić, Nemanja; Rašković, Vera; Cvijanović, Vojin; Đukić, Vojin (Economics of Agriculture, 2022)
Organic agriculture in Serbia is represented by only 0.4% of total agricultural production, which places Serbia at the back of list of European countries and countries in the region. Such production should be part of a rural development strategy. The aim of this work was to establish what would be the motivation of young people to start organic production, on which the perspective of this production depends. A survey conducted on 100 young people, students of the Unit for Agricultural and Business Studies and Tourism was used as a method of work. The results of the survey were summarized, presented as a percentage and described. The results of the survey indicate that 70% of respondents would like to engage in organic plant production, primarily due to the production of high quality food and environmental protection. However, the main shortcomings are insufficient information, insufficient financial support, difficult plant protection and insufficiently organized purchase of products. Most young people would choose to engage in fruit growing (53%).